Comparison of nondestructive testing techniques for the inspection of wind turbine blades' spar caps - Martin, Robert W.; Sabato, Alessandro; Schoenberg, Andrew; Giles, Robert H.; Niezrecki, Christopher (Wind energy (Chichester, England), 2018)
To increase the energy conversion efficiency and power production, the size of wind turbine blades has continued to grow larger. As such, the need to identify defects and monitor the structural health becomes more critical to maintain reliability and prevent costly catastrophic failures. Larger blades are subject to an increased likelihood of operational damage and manufacturing defects. Usually, glass‐reinforced spar caps are inspected with the assistance of strong flashlights, while nondestructive testing (NDT) inspections are performed only on carbon‐reinforced blades which are not translucent. These operations provide qualitative information only. Therefore, there is a growing need for inspection techniques that can provide quantitative information for assessing the structural health of the blades. In recent years, different NDT techniques capable of accurately delivering surface and internal data have been developed. Nondestructive testing systems should be able to quickly and efficiently scan large areas, to be economically beneficial to the wind turbine manufacturing industry. Within this paper, 3 different NDT techniques for the inspection of manufactured wind turbine blades' spar caps are compared: terahertz inverse synthetic aperture radar, infrared thermography, and X‐ray imaging. Each is investigated to evaluate their ability to detect the presence of defects of concern that are created during the blade manufacturing process. Through a set of experimental tests, the advantages, challenges, and drawbacks of each used technique are evaluated and compared in the context of the needs of the wind turbine industry. This research provides the foundation of empirical comparisons that can lead to the development of more accurate NDT resulting in the construction of more reliable and less‐expensive wind turbine blades.